New Thiazole Derivatives: Potent Antifungal against Candida albicans, with silico Docking Unveiling Key Protein Interactions - Omer, Rebaz A.; Ahmed, Karzan M.; Othman, Khdir A.; Hamad, Wali M.; Faraj, Rahman K.; Muhialdin, Ali J.; Salih, Shalaw K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
While bacterial superbugs have garnered much attention, the rise of antifungal resistance poses a growing threat. This study explores the potential of newly synthesized 2,5-Bis(3,4 Dialkoxy Phenyl) Thiazolo[5,4-d] Thiazoles (DATTn compounds) as antifungal agents. Notably, DATTn compounds demonstrated significant fungicidal activity against Candida albicans, a major fungal pathogen, whereas remaining largely ineffective against common bacterial strains, such as Staphylococcus aureus and Escherichia coli. In silico docking simulations using Schrödinger suites unveiled the molecular basis for this selectivity, revealing strong interactions between DATTn molecules and a crucial fungal protein (Portion Data Bank ID: 8JZN) in C. albicans. These findings highlight the potential of DATTn compounds as promising leads for the development of novel antifungal therapies, particularly in light of escalating drug resistance concerns.